Strategic decision-making, marketing investments, and game theory: Optimal competitive strategies between Coca-Cola and Pepsi - Tomić, Daniel (Oeconomica Jadertina, 2026)
The market rivalry between Coca-Cola and Pepsi throughout history represents a paradigmatic example of dynamic and long-standing competition within the soft drink industry. Although both companies offer similar products and target the same market segments, their business models and strategies differ significantly. Over the years, PepsiCo has benefited from early diversification, expanding its portfolio to include non-carbonated beverages and snack products, while Coca-Cola has remained strongly focused on the carbonated beverage segment, relying on global brand recognition and a traditional marketing approach. Despite their differing strategies, both companies continuously adapt their business models to respond to changing consumer preferences, making them a fascinating example of long-term corporate rivalry. This research is motivated by the need for a deeper understanding of the complex aspects of competitive dynamics between Coca-Cola and PepsiCo, particularly in the context of marketing investments and their role in ensuring market dominance. Despite extensive literature on market competition, the scientific research environment has not yet fully utilized the theoretical frameworks of game theory to analyze the strategic decisions of these companies. Therefore, the aim of this study is to model the market interaction between Coca-Cola and Pepsi through the Prisoner’s Dilemma game, applying three key strategies: maintaining equal investment, reducing investment, and increasing investment in marketing activities. The analysis is based on empirical data on marketing investment costs for the period 2014–2023, enabling a quantitative modeling of competitive decisions. Additionally, the study explores the possibility of extending the model through the application of mixed strategies, allowing for a more realistic simulation of uncertainty and changing market conditions. The findings of this research can serve as a foundation for making optimal investment strategies, where corporate decisions will not only impact their individual profitability but also shape the overall market dynamics of the soft drink industry. Expanding the model to include multiple players, including other major competitors in the soft drink industry, could further enhance the understanding of market competition.